Review on guideline pertaining to flood resistance design for residential architecture in Malaysia and UK - Sharika Tasnim,; Nayeem Asif,; Razali Aripin, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Flooding is a crucial issue for structures all around theglobe. The classification and evaluation of damage methods and the  design  of  strategies  to  optimize  flood  resilience  are  thus  critical  components  of  flood  risk  management.  The  paper presents an in-depth analysis of the guideline for flood resistance design for residential architecture in Malaysia and the UK. Both Malaysia and the UK are at risk of flooding because of rainfall and rising sea levels surrounding their  coastal  cities  due  to  climate  change.  Qualitative  research  methodology  is  adopted  for  this  research  by  analysing  the  contents  of  guidelines  of  Malaysia  and  the  UK.  Therefore,  it  has  implemented  content  analysis  from secondary  sources,  including  documents,  briefing  papers,  studies,  and  print  and  online  sources  of  building  and  planning guidelines. The output  from  this  paper  is  that  there  are  measures  of  flood  resistance  design  in  Malaysia.  Measures  include  design  strategies  such  as  using  floodproof  materials,  avoiding  floodplain  zones  for  residential  properties,  etc.  However,  those  measures  are  insufficient  and  need  to  be  more  comprehensive  on  floodresistant  residential  buildings  in  Malaysia.  The  output  from  this  paper  also  compares  the  guidelines  on  flood  resistance design for residential architecture and the different approaches incorporated between Malaysia and the UK. It  needs  further  exploration  of  why  there  is  an  inadequate  effort  to  develop  guidelines  for  residential  architecture  despite considerable residential property damages occurring yearly due to flooding in Malaysia.